1990
DOI: 10.1128/jvi.64.9.4232-4241.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cytolytic T-lymphocyte responses to respiratory syncytial virus: effector cell phenotype and target proteins

Abstract: Cytolytic T-lymphocyte (CTL) activity specific for respiratory syncytial (RS) virus was investigated after intranasal infection of mice with RS virus, after intraperitoneal infection of mice with a recombinant vaccinia virus expressing the F glycoprotein, and after intramuscular vaccination of mice with Formalin-inactivated RS virus or a chimeric glycoprotein, FG, expressed from a recombinant baculovirus. Spleen cell cultures from mice previously infected with live RS virus or the F-protein recombinant vaccini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…To our surprise F‐specific protective T cell immunity waned most rapidly, while both M2 and G specific memory T cells eliminated virus from most mice as late as 100 days after RSV priming. This suggests a different hierarchy of protective pulmonary T cell responses in vivo compared to that defined by restimulation of spleen cells in vitro 29, 40, 41. Interestingly, there were no significant differences in the ability of T cells induced by alocalized pulmonary infection to control virus given via the same route vs. systemically.…”
Section: Discussionmentioning
confidence: 91%
“…To our surprise F‐specific protective T cell immunity waned most rapidly, while both M2 and G specific memory T cells eliminated virus from most mice as late as 100 days after RSV priming. This suggests a different hierarchy of protective pulmonary T cell responses in vivo compared to that defined by restimulation of spleen cells in vitro 29, 40, 41. Interestingly, there were no significant differences in the ability of T cells induced by alocalized pulmonary infection to control virus given via the same route vs. systemically.…”
Section: Discussionmentioning
confidence: 91%
“…We elected to employ A20.J cells as the potential CTL targets on the basis of a number of criteria. A20.J cells are both MHC class I ϩ and II ϩ , thus allowing recognition by CD8 ϩ and CD4 ϩ CTL effector cells (24,34). Demonstrated cytolysis of A20.J targets by vMC 24 -specific bulk-cultured CD4 ϩ T cells would further substantiate an in vivo model in which cardiovirus-infected B cells are killed, suppressing a notable humoral response.…”
Section: Discussionmentioning
confidence: 99%
“…RSVspecific memory cytotoxic T cells have been detected in the spleen of mice after intranasal infection with live virus and intraperitoneal priming with inactivated vi-rus [Bangham et al, 19851. Several epitopes on the virus appear to be T cell stimulating sites Cannon and Bangham, 1989;Nicholas et al, 1990;Openshaw et al, 19901. Little is known about the distribution of T cell subsets and function in the mucosal tissues during primary RSV infection. The only study to date showed that CD8+ cells predominate in bronchoalveolar lavage fluid of mice recovering from RSV infection [Openshaw, 19891. The present studies were undertaken to examine the development and distribution of T cell subsets in the mucosal tissues after primary RSV infection.…”
Section: Introductionmentioning
confidence: 99%